(untitled) (Pedagogy of Higher and Secondary Education, 2011)
In the article possibility of discussion, the use is shown as a method of future teachers’ preparation to forming of intellectually-emotional culture for the children of school collective. An example of employment organization is made on-course "Ecological chemistry" for the students of chemical specialty of pedagogical and other directions of education.